Campesinato negro: conflito e luta pelo acesso e permanência na terra no Baixo Sul da Bahia (1950-1985) - Silva, Egnaldo Rocha da (2018)
Brazil is known for the sad reality of being both the country with the highest land concentration in the world and, contradictorily, one of the countries that has not yet implemented an agrarian reform. Throughout Brazilian history, the agrarian issue has been shown to be a lever of social conflicts and a source of inequalities, victimizing the poor and black population whose colonial project and later republican state project led by the country’s elites has endeavored to promote interdiction and actions to prevent access to land to this population. This research aims at understanding and problematizing the experiences of the black population regarding their access and permanence in the land in the post-abolition period (1950-1985). Its main focus is to investigate the expropriation processes of lands (land grabbing) occupied by black families who live on the area of the current Bahia municipalities of Ituberá, Gandu and Igrapiuna, located geopolitically in the Southern Bahia Lowlands, gateway to the cocoa region. It is a territory of countless agrarian conflicts, involving former land delegates, who were state agents and who played a very important role in the processes of expropriation, land grabbing and de-structuring of black territorialities, many of which constituted in the colonial/imperial period from the formation of quilombos. The primary sources that subsidized this research consisted of of maintenance and reintegration processes of land tenure as well as interviews with descendants of former squatters and/or the squatters themselves and with people who were directly or indirectly involved in the actions that led to land dispossession of the invaded and invaders of land. In this way, this research focuses on three research lines structured from the following issues: 1. how and what strategies were applied in the struggle of the black population in the post-abolition period to get access to land and to resist the action of land grabbers and remain in their land, in many cases even litigating in court actions of maintenance and reintegration of land tenure?; 2. what resources were used by farmers, entrepreneurs and politicians to take possession of lands occupied by black families and how the actions of agents and local public officials have contributed to this process?; and, finally, 3. how did the set of agrarian laws of Bahia, published between the late nineteenth century and the 1980s gave legal support to the actions of farmers and entrepreneurs in land dispossession?